Factors affecting gentamicin assay. - Nilsson, L (1980)
Measurements of gentamicin concentrations in serum by the luciferase method are affected by sodium phosphate, glucose, and heparin. The effects of the first two factors can be eliminated by omitting phosphate and increasing the level of glucose in the culture medium. The effects of heparin cannot be easily circumvented, thus precluding use of this agent as an anticoagulant. Bilirubin, which purportedly inhibits measurement of gentamicin in serum by the disk diffusion assay, does not affect the accuracy of the luciferase method.